PERBANDINGAN POSISI TEGAK (UPRIGHT) DAN ACTIVE BIRTH TERHADAP LAMANYA KALA I PERSALINAN PADA IBU PRIMIPARA - Nina Fitri; Olivia Putri Gumanti (Universitas Fort de Kock Bukittinggi, 2022)
The Demographic and Health Survey results in 2012 showed there was a significant increase in MMR (359 / 100,000 live births). But AKI again showed a decrease (305 / 100,000 live births) based on the results of the 2015 Intercensal Population Survey (SUPAS) (Indonesian health profile, 2016). The Number of Mother Mortality in West Sumatra in 2016, they were 107 people. It was decreased when it was compared in 2015 (111 people). The details of maternal mortality consisted of the death of 30 pregnant women, 25 maternal deaths and 52 postpartum deaths. (Padang Health Office, 2016). The type of research used was quasi-experimental with non-equivalent control group design. The populations were 24 primiparous mothers who were going to have a Maternal Birth Maternal Neti Padang Midwife. Purposive sampling technique with inclusion and exclusion criteria had been used to choose the sample. Then, there 7 multiparous mothers with upright mothers and 7 mothers with active birth positions were chosen as the samples of the research. It was conducted in July 2018. The data was collected trough a patograph sheet as a basis for observation. Then, it was analyzed by univariate and bivariate analysis with Mann-Whitney statistical test. The statistical test results obtained that an average value of the first time the active phase in primiparous mothers with upright position was 318 minutes. While, the average time period I was active in primiparous mothers with active birth position for about 367 minutes. Then, the upright position (upright) and active birth obtained P= 165 where p-value> 0.05. It can be concluded that the upright position and the active birth position did not have much difference to the acceleration of labor during the active phase. Keywords : Acceleration of Labor, Upright, Active Birth